Frances : The Remarkable Story of Princess Diana's Mother - Riddington, Max and Naden, Gavan (London Michael O'mara Books Ltd., 2003)
Chronicles the life of Frances Shand Kydd, mother of Princess Diana, through April of 2003, and tells how she dealt with divorce, adultery, and tragedy.
Include Illustration and Index
Keywords: Upper class -- Families -- Diana, Princess of Wales, 1961-1997